On Track : An exhibition of art in technology - Ferguson, Bruce (Calgary : Olympic Arts Festival, 1988)
Adams, Kim ; Anderson, Laurie ; Borofsky, Jonathan ; Cohn, Norman ; Geleynse, Wyn ; Miller, Branda ; Paik, Nam June ; Steinman, Barbara ; Ferguson, Bruce ; etc.
On Track : An exhibition of art in technology / Une exposition de l'art à l'heure de la technologie, Olympic Arts Festival, Immeuble NOVA Building, Calgary, January 26 - February 28, 1988
boek